The effects of seductive details and topic interest on learning and cognitive load in hypertext environments - Aydın, Yiğit. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The purpose of this study is to investigate whether or not the seductive details effect and topic interest has any effect on learning and cognitive load in hypertext environments. Four types of treatment were designed: hierarchical and network hypertext, with and without seductive details. Data were collected from 109 participants who were undergraduate college students. Participants took a prior knowledge test and topic interest survey then they used the treatment they were assigned. Cognitive load questionnaire, a free recall test and five transfer questions were administered after the treatment. Analyses showed that seductive details seemed to facilitate recall performance whereas higher topic interest led to better transfer performance. On the other hand, hypertext structure has no effect on learning measures as well as on cognitive load. Participants possessing higher prior knowledge were more successful on both learning measures. However, cognitive load did not seem to be affected by any of the independent variables. Results were interpreted in terms of Kintsch’s (1988) construction-integration model of text comprehension and cognitive theory of multimedia learning (Mayer & Moreno, 1999).
Keywords: Hypertext systems.; Cognitive learning theory.